2008
DOI: 10.1021/es800232r
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence for Rejuvenation of Phosphorus Retention Capacity in EAF Steel Slag

Abstract: The purpose of this research was to investigate phosphorus (P) retention capacity and rejuvenation potential of electric arc furnace (EAF) steel slag from Quebec and New Zealand (NZ) iron melter slag (IMS). Columns filled with slag materials were fed with dairy effluent and subjected to two feeding and one resting cycle(s). P retention capacities and rejuvenation potentials were determined after each feeding cycle. Elemental composition and mineralogical analysis were performed on IMS samples. Finally, chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 13 publications
3
39
1
Order By: Relevance
“…Similarly, Weber et al [19] reported that there was not a significant difference in the DRP loading rates and removal efficiencies between filters fed with wastewater that had been pretreated by a constructed wetland (75%) versus untreated effluent (72%) ( Table 1). However, the filters fed with pretreated effluent (at lower TSS loading rates) had a 2.2 fold longer life-span then filters fed without a constructed wetland pretreatment [18,19].…”
Section: Drp Mass Loading Ratesmentioning
confidence: 96%
See 4 more Smart Citations
“…Similarly, Weber et al [19] reported that there was not a significant difference in the DRP loading rates and removal efficiencies between filters fed with wastewater that had been pretreated by a constructed wetland (75%) versus untreated effluent (72%) ( Table 1). However, the filters fed with pretreated effluent (at lower TSS loading rates) had a 2.2 fold longer life-span then filters fed without a constructed wetland pretreatment [18,19].…”
Section: Drp Mass Loading Ratesmentioning
confidence: 96%
“…Drizo et al [18] recently provided a description of the chemical composition of this material. Based on the previous research conducted at the UVM CWRC [18,19] two different particle sizes of EAF steel slag material were employed: 5-10 mm and 10-20 mm, with the larger size used at the inlets to reduce the incidence of clogging. Slag particles were weighed and added to the filters in layers approximately 0.05 m in height.…”
Section: Eaf Steel Slag Filters Constructionmentioning
confidence: 99%
See 3 more Smart Citations